Analisis Habituasi Ratib Al Haddad dalam Meningkatkan Kecerdasan Emosional dan Spiritual - Ruzakki, Hasan; Zainuddin, Zainuddin; Hosaini, Hosaini; Heryandi, M. Tubi (Jurnal Keislaman, 2024)
Learners today are often trapped with easy access to all kinds of information they want. In summary, there are many ways and media to support intellectual aspects. But minimal in emotional and spiritual aspects. Whereas the main support in the intellectual is emotional and spiritual, because emotional readiness determines the success of education even in education. Forming emotional and spiritual intelligence through habits takes time and consistent commitment. Positive habits are needed to form both. One of them is the habit of reading Ratib Al Haddad. This type of research is descriptive qualitative research using systematic literature review (SLR) literature sources. The stages in mapping the literature used in this study were identification, screening, eligibility, and inclusion. Based on the results of research studies from 2014 to 2022 on articles about Ratib Al Haddad's dhikr, emotional and spiritual intelligence, there is a strong focus on strengthening emotional intelligence and spiritual intelligence through habituation of Ratib Al-Haddad, so as to improve students' emotional and spiritual , because the dhikr contains the benefits of remembering Allah SWT and building good emotional character for students, so that they are obedient and obedient to the rules set by the school, especially in the learning process that occurs in class and outside the classroom.